Dinâmica não linear e projeto de controle em sistemas de transporte vertical: comportamentos periódicos e caóticos - Santo, Douglas Roca [UNESP] (2015)
The explosive growth of large urban centers allied to financial limited resources and pressure from increased demand, has forced the cities to develop prodominantly in the vertical direction with the construction of tall buildings (skyscrapers). To supply the demand of these constructions, the development of high speed elevators became a necessity. For high speed passenger's elevators, it is important to considerer passenger's safety and confort. Current research has focused attention on the horizontal and vertical vibration levels inside the cabin and oscillations of the elevator acceleration is usually caused by deformations and misalignments of the guide rails and disturbances caused by the air flow around the cabin. To improve passengers' travel quality, elevators should feature a good feature a good monitoring and control system in order to increase the positioning accuracy and set speed limits not to cause passengers discomfort, decreasing vertical and horizontal vibrations of the elevator cabin. This research aims on studuing and controlling the dynamic horizontal behavior of a three degree of freedom model of a vertical transportation system excited through guide rail deformations. The stiffness of the translational spring equivalent to the tilting motion of the cabin is modeled as a Duffing-type spring. Motivated by the necessity to improve passengers' comfort level, the State-Deéndent Ricatti Equation method is used as a strategy to control the horizontal vibrations and accelerations. Next, we perform extensive numerical simulations studied of the nonlinear behavior of the adopted mathematical model